2019
DOI: 10.1097/apo.0000000000000251
|View full text |Cite
|
Sign up to set email alerts
|

Compared Near-Vision Testing With the Nintendo 3DS PDI Check Game on the Thai–Burma Border

Abstract: Background: A near vision game has been developed for the autostereoscopic screen of the Nintendo 3DS console. Ease of use and time for testing by non–English-speaking patients was not known. Methods: Adult and pediatric patients in a remote Burma clinic were compared with US military staff with each performing conventional near acuity, Stereo Fly, and Ishihara color in addition to PDI Check game, so results could be correlated and timed. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“… 4 Near monocular visual acuity, stereopsis and color vision can be screened in normal military staff and also in remote, non-English speaking villagers. 5 PDI Check correlates well with conventional near vision tests and helps identify ocular suppression both through stereo deficiency, but also with autostereoscopically presented, rivalry near optotypes. 6 Champion shotgun shooters demonstrated extraordinary red-cone and blue cone detection with PDI Check compared to age-matched normal subjects.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“… 4 Near monocular visual acuity, stereopsis and color vision can be screened in normal military staff and also in remote, non-English speaking villagers. 5 PDI Check correlates well with conventional near vision tests and helps identify ocular suppression both through stereo deficiency, but also with autostereoscopically presented, rivalry near optotypes. 6 Champion shotgun shooters demonstrated extraordinary red-cone and blue cone detection with PDI Check compared to age-matched normal subjects.…”
Section: Introductionmentioning
confidence: 76%
“…It is not simple to collect large numbers of color deficient individuals due to the relative rarity of the condition. 5 We did not yet include patients with acquired color defects. We defined color cone deficiency by Innova Rabin method that may not exactly represent FM 100 or anomaloscope.…”
Section: Discussionmentioning
confidence: 99%
“…The Army volunteers previously had faster and better performance than villagers from a remote region in Burma. 7 In another recent validation study, normal color-vision civilian volunteers demonstrated the rapid capacity for PDI Check to identify inherited protanomaly and deuteranomaly compared to Innova Rabin industry-standard computerized testing. 9 The PDI Check scores did not definitively predict eye dominance with stereo or monocular performance in shotgun shooters with a sample size of 29.…”
Section: Discussionmentioning
confidence: 99%
“…9 Former PDI Check color validation studies utilized Ishihara color plates as controls with few color deficient subjects and are much less rigorous since Ishihara is more of a screening test, and not a quantitative test of color. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation